A condition called love. 4 - Morino, Megumi (Morino, Megumi. Hananoi kun to koi no yamai., 2023)
"Hotaru and Hananoi-kun are officially dating now and it's time to go their first real date as a couple! Hotaru is still worried she's not cut out for romance, but little does she know, her new boyfriend is haunted by his own past, too ..."--Back cover